Genomics‐informed design of loop‐mediated isothermal amplification for detection of phytopathogenic Xanthomonas arboricola pv. pruni at the intraspecific level. (2nd July 2012) - Bühlmann, A.; Pothier, J. F.; Tomlinson, J. A.; Frey, J. E.; Boonham, N.; Smits, T. H. M.; Duffy, B.
<x xml:space="preserve">Abstract</x> The objective of this study was to develop a rapid, sensitive detection assay for the quarantine pathogen Xanthomonas arboricola pv. pruni, causal agent of stone fruit bacterial spot, an economically important disease of Prunus spp. Unique targets were identified from X. arboricola pv. pruni genomes using a comparative genomics pipeline of other Xanthomonas species, subspecies and pathovars, and used to identify specific diagnostic markers. Loop‐mediated isothermal amplification (LAMP) was then applied to these markers to provide rapid, sensitive and specific detection. The method developed showed unrivalled specificity with the 79 tested strains and, in contrast to previously established techniques, distinguished between phylogenetically close subspecies such as X. arboricola pv. corylina. The sensitivity of this test is comparable to that of a previously reported TaqMan™ assay at 103 CFU mL−1, while the unrivalled speed of LAMP technology enables a positive result to be obtained in <15 min. The developed assay can be used with real‐time fluorescent detectors for quantitative results as well as with DNA‐staining dyes to function as a simplified strategy for on‐site pathogen detection.